Queer Voices - Nadine Gibson; Ann Rotchford; Addie Sayers (Journal of Effective Teaching in Higher Education)
This study explores queer-spectrum and trans-spectrum students’ voices on establishing a sense of belonging in the classroom. This study contributes to a growing body of research on the experience of queer-spectrum and trans-spectrum students in higher education institutions. Using long-form interviews with 25 students and alumni of a public research university in North Carolina, we find that the incorporation of small gestures by faculty has an outsized impact on fostering a sense of belonging among queer-spectrum and trans-spectrum students. Specifically, small gestures such as the use of preferred pronouns went a long way in making students feel welcomed in the classroom. More broadly, queer-spectrum and trans-spectrum students who identified with their gender assigned at birth also used the use of pronouns by professors as a cue. By virtue of professors taking the time to revise their email signatures, revise their syllabi to include language regarding anti-discrimination and scholarship by a diverse set of scholars, and make a welcoming statement aimed at establishing a safe space for queer-spectrum and trans-spectrum students, signaled to students that they were an ally.